Istinto di morte e conoscenza, 40 anni dopo. Roma, 29 luglio 2010. “Lungo il Tevere Roma” - Vari, Autori (Il sogno della farfalla, 2011)
During the presentation of Death Instinct and Knowledge by M. Fagioli held on the 29th July 2010 at the stand of the “Rinascita” bookshop on the banks of the Tiber River in Roma, Matteo Fago and Noemi Ghetti introduced the text from the point of view of the publisher and classical studies scholar, whilst the psychiatrists Andrea Filippi, Tiziana Amici and Barbara Pelletti offered a reading based on their psychiatric experience, trying to describe how Death Instinct and Knowledge has been of pivotal importance in clinical practice for its proposition of a cure for mental illness through psychotherapy and the interpretation of dreams.